Plant growth-promoting potential of bacterial isolates from the rhizosphere of Deschampsia antarctica - Maslovska, Olga; Komplikevych, Solomiia; Danylo, Iryna; Parnikoza, Ivan; Hnatush, Svitlana (Ukrainian Antarctic Journal, 2024)
Plants’ adaptations, in combination with the rhizosphere and endosphere microbiome, ensure their survival in the extreme conditions of the Antarctic. The work aimed to quantify the culturable microorganisms of different groups and establish the plant growth-promoting potential of bacterial isolates from the rhizosphere of Deschampsia antarctica. Standard microbiological methods (enumeration of microorganisms and study of the properties of isolates, in particular, the cell wall organization by Gram staining, motility, endospore formation, growth at different temperatures, halotolerance, need for oxygen, ability to assimilate some organic carbon sources) and biochemical methods to determine the properties of isolates (oxidase, catalase activities, tests for the ability to reduce nitrate, produce amylases, lipases, proteases). The ability of the isolates to produce siderophores was determined using a medium with chromazurol S and hexadecyltrimethylammonium bromide, to solubilize insoluble phosphate-containing compounds using Pikowska’s medium with Ca3(PO4)2 and Menkina’s medium with egg lecithin. The content of auxin-like substances in the medium was determined by the Salkowski method. The effect of the isolates on wheat growth was determined by the germination of wheat seeds treated with the isolates, the length of shoots and roots of plants, and chlorophyll content in leaves. The isolates were identified using phylogenetic analysis of the 16S rRNA gene. The most abundant groups of microorganisms in the rhizosphere of D. antarctica were oligotrophic, oligonitrophilic, and cellulose-degrading microorganisms. Among 120 isolates of the rhizosphere zone of D. antarctica, 7 oligonitrophilic isolates (RE1, RE3, RE4, RE8, RP8, RO4, RT1) were selected, which solubilized insoluble phosphate-containing compounds, synthesized lipases, amylases, auxin-like substances, and siderophores. Isolate RT1 (Bacillus sp. RT1 by physiological and biochemical properties and the 16S rRNA gene) showed the best plant growth-promoting properties. Treatment of wheat seeds with this isolate increased germination by 25%, shoot and root length by 15%, leaf area 3 times, and chlorophyll content 1.6 times.